IMPACTS: Framework for Risk Assessment of CO2 Transport and Storage Infrastructure. (July 2017) - Brown, A.; Eickhoff, C.; Reinders, J.E.A.; Raben, I.; Spruijt, M.; Neele, F.
Abstract: There is an urgent drive to implement Carbon Capture and Storage (CCS) on a commercial and global scale. This needs to be done in a demonstrably safe and responsible manner that gains widespread acceptance of stakeholders, most notably regulators and the public. If inhaled in sufficiently high concentrations, CO2 can have toxicological effects on the human body. The hazardous aspects of CO2, combined with the very large quantities that will be contained within CCS systems create the potential that a leak from a CO2 system could pose a major accident hazard. The CO2 stream from capture plants will not be 100% pure, but contain substances, referred to as stream impurities, such as CO, H2 O, H2 S, NOx, SOx, O2 and H2 that, although in very low levels, can change the properties of the CO2 stream and can change the likelihood and/or the consequences of CO2 system leaks. The IMPACTS project is concerned with the impact these impurities may have when present in CO2 transport and storage systems. The risks associated with CO2 captured as a result of CCS operations differ from those previously encountered either in Natural Gas pipelines or in pure CO2 pipelines (used in USA and elsewhere for enhanced oil recovery operations) in a number of ways, but particularly on account of the large volumes, high pressures and nature of the impurities involved. Established techniques can be used to determine the risks from events that would undermine the overall integrity derived from the design, manufacture, construction and operation of the infrastructure. Some of these techniques and the assessment thereof have been described, together with consequences that can be expected, based on industry experience with pipelines other than those transporting impure CO2 . Some of the event types that can lead to a reduction in the level of safety of transport and storage of large volumes of impure CO2, under high pressure, have been identified, and the associated risks described. A significant amount of information, including guidelines, industry standards and legislation, exists worldwide and provides decision support for the design of pipelines carrying hazardous materials. This includes risk reduction measures, requirements for risk assessment, risk criteria and the need for further risk reduction. However, in most cases CO2 is not currently in the scope, but it is possible to apply many of the principles therein to pipelines containing CO2, albeit with some caution. In the absence of agreed guidance figures, reference is made to standards that could be used in system design to support a Safety Case to demonstrate that the risks are at an acceptable level. It would be hoped that these will serve to stimulate debate and provide a starting point from which an acceptable balance might be found between applying additional measures to improve safety by design, and providing projects that are affordable, at the same time allaying public concerns implicit in the introduction of new technologies. At the same time an ISO Standard for CCS is being produced, and this also attempts to provide necessary guidance for system designers.